The Genus Alexandrium (Dinophyceae, Dinophyta) in Brazilian Coastal Waters - Menezes, Mariângela; Branco, Suema; Miotto, Maria Cecília; Alves-de-Souza, Catharina (Frontiers in Marine Science, 2018)
A review of the dinoflagellate genus Alexandrium occurring in Brazilian coastal waters is presented based on both published information and new data. Seven Alexandrium species have been recorded from Brazil so far: A. catenella, A. fraterculus, A. gaardnerae, A. kutnerae, A. tamiyavanichi, A. tamutum, and Alexandrium sp. While A. gaardnerae and A. kutnerae were identified based only on morphological characteristics, phylogenetic analysis (ITS and LSU rDNA) were performed for the remaining species based on cultures and/or field populations. Monoclonal cultures of the analyzed species were isolated from field samples obtained from Bahia (A. tamiyavanichi, two strains), Rio de Janeiro (A. tamutum, three strains; Alexandrium sp., two strains), Santa Catarina (A. fraterculus, one strain) and Rio Grande do Sul (A. tamarense, three strains). This is the first record of A. tamutum for the South Atlantic. In addition, molecular data for Brazilian strains of A. fraterculus are presented for the first time, as well as sequences from the ITS region for A. catenella (previously reported as A. tamarense) from Brazilian coastal waters. The morphological characters of the three species corresponded to those typically recorded in the literature and their identification was confirmed by molecular analysis. Based on the LSU rDNA and ITS regions, the three strains of A. catenella showed a high degree of similarity with strains from Southern Chile and North America. The implications and limitations of these findings for the monitoring protocols within the global and regional context are discussed.